2021
DOI: 10.1080/19490976.2021.1927635
|View full text |Cite
|
Sign up to set email alerts
|

Engraftment of strictly anaerobic oxygen-sensitive bacteria in irritable bowel syndrome patients following fecal microbiota transplantation does not improve symptoms

Abstract: Dysbiosis of the gut microbiome has been correlated with irritable bowel syndrome (IBS). Fecal microbiota transplantation (FMT) is being explored as a therapeutic option. Little is known of the mechanisms of engraftment of microbes following FMT and whether the engraftment of certain microbes correlate with clinical improvement in IBS. Microbiome data, from a previously reported placebo-controlled trial of treatment of IBS with FMT or placebo capsules, were used to investigate microbial engraftment 15 days, 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 55 publications
(83 reference statements)
0
11
0
Order By: Relevance
“…They further analyzed the effect of oral FMT on abdominal pain, stool frequency, and stool form, but found no clinical beneficial effect ( 25 ). In their following study, they found long-term increased anaerobic bacteria in the FMT group, such as Faecalibacterium, Prevotella , and Bacteroides ( 26 ). It is presumed that the changes in the microbiota induced by oral FMT are not significant enough to improve the IBS symptoms.…”
Section: Discussionmentioning
confidence: 86%
“…They further analyzed the effect of oral FMT on abdominal pain, stool frequency, and stool form, but found no clinical beneficial effect ( 25 ). In their following study, they found long-term increased anaerobic bacteria in the FMT group, such as Faecalibacterium, Prevotella , and Bacteroides ( 26 ). It is presumed that the changes in the microbiota induced by oral FMT are not significant enough to improve the IBS symptoms.…”
Section: Discussionmentioning
confidence: 86%
“…A specific selection of a donor who shows enrichment in those bacteria lacking in the recipient ( Lachnospiraceae and Ruminococcaceae ) might represent a good strategy, as exploited in clinical trials on hepatic encephalopathy [ 38 , 137 ]., Moreover, the level of engraftment and long-lasting effect represents the main variables in the successful FMT and clinical outcomes. For example, in IBS the post-FMT engraftment of strictly anaerobic bacteria after FMT does not improve symptoms [ 255 ], while post-FMT engraftment in people with chronic constipation is highly populated by species belonging to the Firmicutes and carries genes related to polysaccharide metabolism [ 256 ]. Certainly, the way of FMT delivery, as well as the number of FMT treatments (for example, one single FMT via colonoscopy is not clinically effective in ulcerative colitis [ 78 ]), might play a role as well, but it has become clear that certain donor’s microbiota profiles are more likely to get a better chance to engraft, colonize and to produce a beneficial effect in the host.…”
Section: Divergent Clinical Response To Fecal Microbiota Transplantat...mentioning
confidence: 99%
“…In the absence of an effective method to restore the dysbiosis, transplanting a microbiome from healthy individuals with well‐functioning guts to those with IBS and dysbiosis (fecal microbiota transplantation [FMT]) is conceivable. In contrast to probiotics treatment, FMT has been found to induce long‐term bacteria colonization in the intestine 18 . FMT has been applied to patients with IBS in seven randomized controlled trials (RCTs), four of which found a positive effect while the other three found no effect 19 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to probiotics treatment, FMT has been found to induce long-term bacteria colonization in the intestine. 18 FMT has been applied to patients with IBS in seven randomized controlled trials (RCTs), four of which found a positive effect while the other three found no effect. 19 It is difficult to compare these RCTs due to variations in the criteria used to select the donors and patients, in the fecal transplant dose used in the FMT, the way the transplant was preserved and prepared, and the administration route.…”
mentioning
confidence: 99%